Employee Perception of Brand Value in the Jewelry Industry - Selvy Priskila; Gede Sri Darma (Universitas Hayam Wuruk Perbanas, 2020)
This study aims to discuss the brand value proposed by John Hardy and, as jewelryretail, it can be seen from each of these brand values. This study uses a qualitativemethod with the interview technique or open questionnaire for gaining all employeesin the sales department of John Hardy, Indonesia. The data were collected andanalyzed by first reducing and presenting the data and finally concluding.Triangulation was also done to get the trustworthiness (data validity) so that it isexpected to provide valid data for research. It shows that community, artisanship, and sustainability are much linked to the brand, and it is also tied together as well as being implemented. For that reason, John Hardy is required to know how to deliver the information correctly to the customer, mention the company's history, the value, and DNA (deoxyribonu-cleic acid) as the individual blueprint of every living thing, which makes it unique in the company.